Exploring the Meaning of Organizational Purpose at a New Dawn: The Development of a Conceptual Model Through Expert Interviews - van Ingen, Ramon; Peters, Pascale; De Ruiter, Melanie; Robben, Henry (Frontiers in Psychology, 2021)
Organizational purpose has flourished in the professional management literature, yet despite increased scholarly interest, academic knowledge and empirical research on the topic remain scarce. Moreover, studies that have been conducted contain important oversights including the lack of a clear conceptualization and misinterpretations that hinder the further development and understanding of organizational purpose. In view of these shortcomings, our interview study aimed to contribute to academic and societal conversations on the contemporary meaning and function of organizational purpose considering the voices and perspectives of 44 global experts. Employing template analysis, we defined organizational purpose as “an organization’s reason for being characterized by significance, aspiration, direction, unification, and motivation.” Moreover, we proposed an explanatory conceptual model, including drivers and outcomes of purpose, important boundary conditions, and explanatory mechanisms. Drawing on self-determination theory, person–organization fit theory, job characteristics theory, and conservation of resources theory, we were able to explain how and under what conditions these concepts are related to organizational purpose. In doing so, our research contributes to advancing the knowledge and understanding of organizational purpose and its effects on human lives within and outside organizations. Our study thereby enhances the understanding of the role of organizations in society and helps in evaluating whether organizations take responsibility by living their purpose in the society they are part of. As such, our study provides important insights for theory development, scale development, and further empirical research on organizational purpose and its effects in different streams such as OB, HRM, marketing, leadership, and strategy.